A sentença proferida em ação de produção antecipada de provas - Luz, Tatiana Tiberio (2024)
The objective of this work is to analyze the sentence handed down in the early production of evidence lawsuit, in relation to its content and whether or not it has the authority of material res judicata. The question proves to be useful as there is no legal provision on the subject and, depending on the answer to this question, it will have effects on the legal sphere of the parties who participated in the lawsuit. To this end, we present considerations about the concept of proof and the principles that guide the production of proof. As a consequence, we developed aspects about the rite of the early production of evidence lawsuit, as its regulation appears to be insufficient in the legal system. From what we have seen, we conclude that the sentence handed down in the early production of evidence lawsuit is covered by the cloak of material res judicata and, therefore, can be rescinded in some of the cases in which a rescission lawsuit is appropriate